Task-based elementary Spanish in rural Indiana: A practice-based collaboration - Gurzynski-Weiss, Laura; Wray, Madison; Coulter-Kern, Mackenzie; Bernardo, Johana (Studies in Second Language Learning and Teaching, 2024)
Spanish is the second most spoken language in the United States and the most taught additional language (L2) in elementary-level schools. However, the amount and type of access differs according to the resources available. Rural settings, which comprise a third of all schools in the US, often have fewer resources and support for the development and maintenance of exposure-track L2 programs, which meet once per week with the goal of, as the name suggests, providing exposure to the L2, rather than a focus on cumulative language development. Given that there are immediate and long-term benefits of even low levels of early bilingualism, ensuring access to quality L2 education is a matter of equity. This paper centers on the first year of a longitudinal collaboration between an exposure-track Spanish language teacher in a rural elementary school, and the research team who created a task-based program tailored for the school following a needs analysis. We analyze the first year of the grant-funded program based on task effectiveness, student enjoyment, and teacher perspectives. We contextualize results within the rural community and offer initial longitudinal data on US exposure-track Spanish. We detail how we adjusted the program for the second year, are freely sharing the materials on the Task Bank (tblt.indiana.edu) and have transferred the program to the teacher’s autonomy. Finally, we highlight that the success of this program was and is due to the collaborative nature of the partnership between the teacher, the researchers, and the administrators.